Estudio de prefactibilidad para la producción y comercialización de vajillas biodegradables - Muñoz Barreto, Duvan Andres; Parra Vivas, Andrés Felipe (Universidad Antonio Nariño, 2021)
The purpose of this degree work is to develop a pre-feasibility study for the manufacture and commercialization of biodegradable tableware, based on avocado seed in the city of Bogotá D.C. The work was carried out using a descriptive quantitative methodology, in which virtual surveys were carried out due to the health problems that the country presents. Data were obtained from the target population to later analyze them and parameterize the analysis variables, to establish how viable it is to start the manufacture and commercialization of biodegradable plastic tableware based on avocado seed. Through the pre-feasibility study, it is sought to determine the requirements and resources to obtain the 100% environmentally friendly product, with the use of natural waste such as avocado seed and other residues, to guarantee the total decomposition of the products. This study allowed an evaluation and analysis of the level of viability and associated risks contained in the implementation and development of the project; This structure is made up of five axes, which are described below: market study, technical study, environmental, administrative and legal study and financial study.